2010
DOI: 10.1016/j.foodchem.2010.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Sterol content in sunflower seeds (Helianthus annuus L.) as affected by genotypes and environmental conditions

Abstract: Phytosterols play essential roles in many plant cell mechanisms. They are of industrial interest since, as part of the diet, they can reduce low density lipoprotein cholesterol. An increase in plant sterol contents, by improved crop varieties or crop management, could help to answer industrial demands and also to develop environmentally friendly extraction methods. The aim of this study was to evaluate genotypic variability of sterol content in cultivated sunflower and, in particular, effects of sowing date. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 21 publications
6
44
1
1
Order By: Relevance
“…'Hysun-33' attained significantly higher protein content (18.23%) than 'S-278' (17.10%), which might be due to varying genetic potential of the hybrids. These results are in accordance with the findings of Roche et al (2010) and Bukhsh et al (2011) that different sunflower hybrids exhibit the differential response to protein content in achene due to their difference of genetic makeup.…”
Section: Achene Protein Contents (%)supporting
confidence: 93%
See 1 more Smart Citation
“…'Hysun-33' attained significantly higher protein content (18.23%) than 'S-278' (17.10%), which might be due to varying genetic potential of the hybrids. These results are in accordance with the findings of Roche et al (2010) and Bukhsh et al (2011) that different sunflower hybrids exhibit the differential response to protein content in achene due to their difference of genetic makeup.…”
Section: Achene Protein Contents (%)supporting
confidence: 93%
“…The effect of the year was also not significant. These results are consistent with the findings of Roche et al (2010) and Bukhsh et al (2011), who found that different sunflower hybrids exhibit distinct responses to oil content in achene due to differences in their genetic makeup.…”
Section: Achene Oil Contents (%)supporting
confidence: 93%
“…Sunflower seeds are achenes. They contain about 45% oil, which is harvested mostly for human consumption, but also for use in industry, particularly in Correspondence: zephirin.mouloungui@ensiacet.fr the production of biofuels and biolubricants (Ballerini, 2006;Roche et al, 2010). France is the main consumer and producer of sunflower in the European Union.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the fluidity of the fatty acids in cell membranes depends on the rate of lipid desaturation: the maintenance of correct fluidity requires lower rates of desaturation at higher temperatures than at lower temperatures. Several studies have shown that oleic acid content increases with cumulative temperature during peak lipogenesis activity (Roche et al, 2006(Roche et al, , 2010Baud and Lepiniec, 2010;Merah et al, 2012). It may, therefore, be necessary to modify cropping practices when growing "technical" varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Broad sense heritability was estimated in 0.72 by Merah, et al (2012) and 0.85 by Velasco, et al (2013). Amongst the main factors influencing seed phytosterol content, Roche, et al (2006;2010b) found that higher temperatures enhanced phytosterol accumulation, whereas water stress has been also found to favour phytosterol accumulation in sunflower seeds (Roche, et al, 2006).…”
Section: Variability For Seed Phytosterol Content In Sunflower Germplasmmentioning
confidence: 96%